A probabilistic inverse prediction method for predicting plutonium processing conditions - Ausdemore, Madeline A.; McCombs, Audrey; Ries, Daniel; Zhang, Adah; Shuler, Kurtis; Tucker, J. Derek; Goode, Katherine; Huerta, J. Gabriel (Frontiers in Nuclear Engineering, 2022)
In the past decade, nuclear chemists and physicists have been conducting studies to investigate the signatures associated with the production of special nuclear material (SNM). In particular, these studies aim to determine how various processing parameters impact the physical, chemical, and morphological properties of the resulting SNM. By better understanding how these properties relate to the processing parameters, scientists can better contribute to nuclear forensics investigations by quantifying their results and ultimately shortening the forensic timeline. This paper aims to statistically analyze and quantify the relationships that exist between the processing conditions used in these experiments and the various properties of the nuclear end-product by invoking inverse methods. In particular, these methods make use of Bayesian Adaptive Spline Surface models in conjunction with Bayesian model calibration techniques to probabilistically determine processing conditions as an inverse function of morphological characteristics. Not only does the model presented in this paper allow for providing point estimates of a sample of SNM, but it also incorporates uncertainty into these predictions. This model proves sufficient for predicting processing conditions within a standard deviation of the observed processing conditions, on average, provides a solid foundation for future work in predicting processing conditions of particles of SNM using only their observed morphological characteristics, and is generalizable to the field of chemometrics for applicability across different materials.